IgM kappa proliferative glomerulonephritis with monoclonal immunoglobulin deposition complicated with nocardiosis dermatitis: a case report and review of literature - Chen, Kebao; Wang, Yue; Yu, Jinyu; Wang, Xueyao; Xu, Zhonggao; Li, Yanbo; Sun, Weixia (Frontiers in Medicine, 2024)
Rationale Monoclonal gammopathy of renal significance (MGRS) represents a group of disorders caused by monoclonal immunoglobulin (M protein) secreted by B cells or plasma cells. Proliferative glomerulonephritis with monoclonal immunoglobulin deposition (PGNMID) is a glomerular disease and a form of MGRS. Here, we presented a rare case of a patient with IgM kappa PGNMID complicated with nocardiosis dermatitis. Patient concerns and diagnoses A 56-year-old man was admitted to the hospital because of cutaneous purpura and proteinuria. His initial pathological diagnosis indicated membranous proliferative glomerulonephritis, IgM(++), and subacute interstitial nephritis. Based on further examination, he was finally diagnosed to have IgM kappa PGNMID and subacute interstitial nephritis. After the initial diagnosis, the patient received hormonal therapy. During the treatment, nocardiosis dermatitis emerged as a complication, and the hormonal therapy was gradually reduced. The patient refused further treatment with rituximab, and his health is currently stable. Outcomes IgM kappa PGNMID complicated with nocardiosis dermatitis is an extremely rare occurrence. Laboratory examination and pathological analysis are required to confirm the diagnosis of this disorder. Timely and accurate diagnosis is essential for the appropriate treatment of PGNMID.